2015
DOI: 10.1002/mgg3.182
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenicity of genetic variants previously associated with left ventricular non‐compaction

Abstract: BackgroundLeft ventricular non‐compaction (LVNC) is a rare cardiomyopathy. Many genetic variants have been associated with LVNC. However, the number of the previous LVNC‐associated variants that are common in the background population remains unknown. The aim of this study was to provide an updated list of previously reported LVNC‐associated variants with biologic description and investigate the prevalence of LVNC variants in healthy general population to find false‐positive LVNC‐associated variants.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As these previously mentioned NUP155 missense mutations as well as dysregulated expression of other discrete nups have been associated with a variety of clinical cardiopathologies (5,10,14), this study was carried out to investigate the prevalence of reported NUP155 variants with potential cardiopathogenicity. To this end, we canvassed variants within the NHLBI Exome Sequencing Project along with data from gnomAD and dbNSFP databases to enhance prioritization of variants potentially implicated in cardiovascular disorders (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…As these previously mentioned NUP155 missense mutations as well as dysregulated expression of other discrete nups have been associated with a variety of clinical cardiopathologies (5,10,14), this study was carried out to investigate the prevalence of reported NUP155 variants with potential cardiopathogenicity. To this end, we canvassed variants within the NHLBI Exome Sequencing Project along with data from gnomAD and dbNSFP databases to enhance prioritization of variants potentially implicated in cardiovascular disorders (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The gene encodes beta‐myosin heavy chain which plays a role in sarcomere formation and cardiac muscle function. Variants in MYH7 have been previously reported in association with a variety of cardiac anomalies including hypertrophic, dilated and restrictive cardiomyopathies, Ebstein anomaly, and left ventricular noncompaction (Abbasi et al., ). The patient was diagnosed with Ebstein anomaly; her father, who has mild Ebstein anomaly, was found to carry the variant as well.…”
Section: Resultsmentioning
confidence: 99%
“…In this novel study, we provide the clinicians the first comprehensive evaluation tool for genetic diagnostic of PAH, by evaluating the allele frequency of previously reported PAH‐associated variants in the two large background population databases (ESP and ExAC), and also by adding in silico prediction analysis using an established conservative method (Abbasi et al., ; Jabbari et al., ; Risgaard et al., ). Surprisingly, in the literature we identified very limited data on familial cosegregation, thus, unfortunately, the familial cosegregation in our evaluation was very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants Nonsense variants BMPR2 86 49 population databases (ESP and ExAC), and also by adding in silico prediction analysis using an established conservative method (Abbasi et al, 2016;Jabbari et al, 2013;Risgaard et al, 2013). Surprisingly, in the literature we identified very limited data on familial cosegregation, thus, unfortunately, the familial cosegregation in our evaluation was very limited.…”
Section: Genementioning
confidence: 99%